DEVELOPMENT OF IN PLANTA TRANSFORMATION METHOD USING Agrobacterium tumefaciens THAT IS SIMPLE AND EFFICIENT AS WELL AS APPLICABLE TO VARIOUS PLANTS - Mineo Kojima (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2013)
A simple and effi cient in planta transformation method was developed. In the method, meristems of eitherapical or axillary buds of immature plants or apical buds of embryos in imbibed seeds, depending on plants,were inoculated by Agrobacterium tumefaciens after being pricked with a needle. The inoculated plants weregrown to maturation in pots under non-sterile conditions. Transformation was demonstrated by severallines of evidence obtained with mostly the progenies of T1 generation; phenotypic inheritance from T0plants to plants of the following generation, resistance of seed germination to antibiotics, detection of?-glucuronidase activity in transformants of T1 generation, detection of transgene by Southern blot andPCR analyses in T1 generation transformants and rescue from T1 generation transformants of the plasmidscomposed of T-DNA of binary vector and fl anking plant genomic DNA. The diverse species of plants such asbuckwheat (Fagopyrum esculentum), mulberry (Morus alba L.), kenaf (Hibiscus cannabinus), rice (Oryza sativa),wheat (Triticum aestibvum L.), maize (Zea mays), and soybean (Glycine max) were shown to be effi cientlytransformed by our in planta method.